Effects of weed control and fertilization on wood and chemi-mechanical pulp properties of a Populus deltoides clone - Villegas, María Silvina (2014)
Weed control and fertilization usually lead to an increase in the growth rate of trees and, consequently, to a possible modification of the quality of the wood and its end products. The effect of weed control and fertilization practices were determined on tree growth parameters, wood density, fiber weight, fiber length, and chemical wood composition, as well as the chemi-mechanical pulp properties, for 8-year-old Populus deltoides `Delta Gold´ grown in Argentina. Four treatments belonging to a randomized complete block design trial were analysed: no weeding after planting (C), mechanical weed control (M), chemimechanical weed control (CHM), and fertilized + chemimechanical weed control (CHM-F). Soda-sulfite chemi-mechanical pulps were produced from said trees. Handsheets were prepared from the pulps, and their physical, mechanical, and optical properties were determined following international standards. Several wood and pulp properties were influenced by the studied silvicultural practices. In the context of this study, silvicultural treatments applied to Populus deltoides ‘Delta Gold’ (formerly ‘Stoneville 66’) trees can be applied to increase productivity (volume and fibrous output) without detrimental consequences to wood and pulp properties, except for a slight reduction in brightness.